2001
DOI: 10.1038/sj.onc.1204432
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of G1/S transition by the candidate bladder tumour suppressor gene DBCCR1

Abstract: Deletion of all or part of chromosome 9q is the most common genetic alteration in all stages and grades of bladder cancer. DBCCR1 (deleted in bladder cancer chromosome region candidate 1) maps to the chromosome region 9q32-33, a candidate tumour suppressor locus for bladder cancer. Although no mutations of DBCCR1 have been detected in bladder tumours, expression of DBCCR1 is silenced by promoter hypermethylation in 50% of bladder cancer cell lines analysed. Here we sought to provide functional evidence to auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 22 publications
2
36
0
Order By: Relevance
“…Previous cell cycle studies suggested that DBCCR1 has growth-suppressing and antiproliferative activities mediated via modulation of the G 1 checkpoint. Overexpression of DBCCR1 caused a slower G 1 transition rather than G 1 arrest and did not affect apoptosis (Nishiyama et al, 2001). Although these functional studies and the high rate of DBCCR1 hypermethylation in oral squamous cell carcinomas support the candidacy of DBCCR1 as a tumour suppressor at 9q33, additional studies are required to unravel its possible role in oral malignant development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cell cycle studies suggested that DBCCR1 has growth-suppressing and antiproliferative activities mediated via modulation of the G 1 checkpoint. Overexpression of DBCCR1 caused a slower G 1 transition rather than G 1 arrest and did not affect apoptosis (Nishiyama et al, 2001). Although these functional studies and the high rate of DBCCR1 hypermethylation in oral squamous cell carcinomas support the candidacy of DBCCR1 as a tumour suppressor at 9q33, additional studies are required to unravel its possible role in oral malignant development.…”
Section: Discussionmentioning
confidence: 99%
“…As the name implies, the gene is frequently deleted in bladder cancer, which has also been reported to be associated with asbestos exposure (22,23). DBC1 has been shown to inhibit cell proliferation by negative regulation of the G 1 -S transition (24). In our previous expression array analysis, we detected low expression of DBC1 in both normal lung and .…”
Section: Chromosomal Microsatellitementioning
confidence: 99%
“…In addition to LOH studies, evidence supporting the hypothesis that DBCCR1 is a tumor suppressor gene includes chromosome copy number changes detected by fluorescence in situ hybridization (FISH) (Stadler et al, 2001), absence of DBCCR1 mRNA expression in tumor cell lines and bladder tumors, and the existence of a bladder tumor (Nishiyama et al, 1999) and a bladder tumor cell line with homozygous deletions at the DBCCR1 locus (9p33) (Fujiwara et al, 2001).Transfection and expression of DBCCR1 in NIH/3T3 cells resulted in an increase in the proportion of cells in the G1 phase of the cell cycle (Nishiyama et al, 2001). This phenomenon was observable only under serum starvation conditions and the mechanism of action remains unclear.…”
Section: Introductionmentioning
confidence: 99%